Optimization of School Finance Based on Pesantren - Sandy, Nurezi Kurnia; Astutik, Anita Puji (Indonesian Journal of Islamic Studies, 2024)
The general background school finance management is a crucial aspect of ensuring the effectiveness and sustainability of educational institutions. Specific Background In pesantren-based schools, financial management is often hindered by limited resources, lack of transparency, and weak human resource capacity. Knowledge Gap There is limited research on optimizing financial management in pesantren-based educational settings, particularly in Muhammadiyah-affiliated institutions. Aims This study aims to explore and develop a model for optimizing school finance management in a pesantren-based educational institution. Results The findings indicate that financial optimization can be achieved through transparent and accountable management systems, the integration of information technology, and enhanced human resource capacity through training and education. Active participation from the school committee and parents in financial oversight is also critical. Additionally, integrating pesantren values such as honesty and responsibility fosters a culture of ethical and integrity-based financial management. Novelty This research introduces the application of pesantren values in financial management as a distinctive approach to enhancing transparency, accountability, and efficiency in school finance. Implications The study’s findings have significant implications for similar institutions, suggesting that the adoption of technological tools and the involvement of key stakeholders can improve financial management. Furthermore, diversifying funding sources through donations, partnerships, and optimizing school assets can ensure the sustainability of educational programs, supporting the institution's mission and vision. Highlights: Integration of pesantren values enhances ethical financial management. Active participation from stakeholders improves accountability and oversight. Diversification of funding sources ensures sustainability of educational programs. Keywords: School Finance, Pesantren, Financial Optimization, Transparency, Educational Sustainability